Reducing daily salt intake in China by 1 g could prevent almost 9 million cardiovascular events by 2030: a modelling study. Issue 2 (16th August 2022) - Tan, Monique; He, Feng; Morris, Joan K; MacGregor, Graham
Abstract : Introduction: In China, salt intake is among the highest in the world (~11 g/day) and cardiovascular disease (CVD) accounts for 40% of deaths. We estimated the potential impact of reducing salt intake on CVD events in China, via systolic blood pressure (SBP). Methods: To develop our model, we extracted the effect of salt reduction on SBP from a meta-regression of randomised trials and a population study, and that of SBP on CVD risk from pooled cohort studies. Results: Reducing population salt intake in China by 1 g/day could lower the risk for ischaemic heart disease by about 4% (95% uncertainty interval 1.8%–7.7%) and the risk for stroke by about 6% (2.4%–9.3%). Should this reduced salt level be sustained until 2030, ~9 million (M) (7M–10.8M) CVD events could be prevented, of which ~4M (3.1M–4.9M) would have been fatal. Greater and gradual salt intake reductions, to achieve WHO's target of 30% reduction by 2025 or the Chinese government's target of ≤5 g/day by 2030, could prevent ~1.5 or 2 times more CVD events and deaths, respectively. Should the prolonged effect of salt reduction over several years be accounted for, all estimates of CVD events and deaths prevented would be 25% greater on average. Conclusion: Bringing down the high salt intake levels in China could result in large reductions in CVD. An easily achievable reduction of 1 g/day could prevent ~9M CVD events by 2030. Urgent action must be taken to reduce salt intake in China.